Ten-year results of the Multicentric Italian Lung Detection trial demonstrate the safety and efficacy of biennial lung cancer screening. (September 2019) - Pastorino, U.; Sverzellati, N.; Sestini, S.; Silva, M.; Sabia, F.; Boeri, M.; Cantarutti, A.; Sozzi, G.; Corrao, G.; Marchianò, A.
Abstract: Background: The Multicentric Italian Lung Detection (MILD) trial demonstrated that prolonged low-dose computed tomography (LDCT) screening could achieve a 39% reduction in lung cancer (LC) mortality. We have here evaluated the long-term results of annual vs. biennial LDCT and the impact of screening intensity on overall and LC-specific mortality at 10 years. Patients and methods: Between 2005 and 2018, the MILD trial prospectively randomised the 2376 screening arm participants to annual (n = 1190) or biennial (n = 1186) LDCT, for a median screening period of 6.2 years and 23, 083 person-years of follow-up. The primary outcomes were 10-year overall and LC-specific mortality, and the secondary end-points were the frequency of advanced-stage and interval LCs. Results: The biennial LDCT arm showed a similar overall mortality (hazard ratio [HR] 0.80, 95% confidence interval [CI] 0.57–1.12) and LC-specific mortality at 10 years (HR 1.10, 95% CI 0.59–2.05), as compared with the annual LDCT arm. Biennial screening saved 44% of follow-up LDCTs in subjects with negative baseline LDCT, and 38% of LDCTs in all participants, with no increase in the occurrence of stage II-IV or interval LCs. Conclusions: The MILD trial provides original evidence that prolonged screening beyond five years with biennial LDCT can achieve an LC mortality reduction comparable to annual LDCT, in subjects with a negative baseline examination. Highlights: MILD trial randomized Annual vs Biennial screening. Biennial screening is safe in subjects with a negative baseline LDCT. Biennial screening avoided 38% of LDCTs. Screening intervals can be based on individual risk profile.